Real time polymerase chain reaction for detecting SARS-COV-2 in Indonesia: are the results reliable? - Hartanti, Monica Dwi (Faculty of Medicine, Trisakti University, 2020)
Since it was first reported in Wuhan, China in December 2019, coronavirus disease 2019 (COVID-19) has been considered as a pandemic. It is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a member of the Coronavirus family. In Indonesia, this disease first detected in the middle of March 2020 and it was spreading all over Indonesia. The Indonesian Government has implemented several strategies in order to detain the spreading of COVID-19, including improving diagnostic management. Until now, the most reliable method of detecting COVID-19 is real time-PCR.